An Empirical Investigation of the Nexus among Money Balances, Commodity Prices and Consumer Goods’ Prices - Grigoli, Francesco (2012)
This paper aims to identify the nexus between the excess of liquidity in the United States and commodity prices over the 1983-2006 period. In particular, it assesses whether commodity prices react more powerfully than consumer goods' prices to changes in real money balances. Within a cointegrated vector autoregressive framework, the author investigates whether consumer prices and commodity prices react to excess liquidity, and if the different price elasticities of supply for goods and commodities allow for differences in the dynamic paths of price adjustment to a liquidity shock. The results show a positive relationship between real money and real commodity prices and provide empirical evidence for a stronger response of commodity prices with respect to consumer goods' prices. This could imply that, if the magnitude of the reaction is due the fact that consumer goods' prices are slower to react, then their long-run value can be predicted with the help of commodity prices. The findings support the view that the latter should be considered as a valid monetary indicator.